2018
DOI: 10.1016/j.arth.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Operating Room Traffic Increases Aerosolized Particles and Compromises the Air Quality: A Simulated Study

Abstract: This study confirms that personnel and door opening are a major source of particles in the OR air. Controlling traffic is critical for reduction of particles and is likely to be a key preventative strategy in reducing periprosthetic joint infection. LAF is protective against the negative influence of number of people and door openings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 28 publications
1
35
0
Order By: Relevance
“…In order to minimize cofounders such as increased particle load due to door opening and number of persons in the OR, those risk factors were standardized [ 19 , 21 ]. Door opening was reduced to a minimum: study nurse entered an empty OR, 2 scrub nurses entered OR to prepare surgical setting, patient and anaesthesiology team (2 persons) entered OR and surgical team entered OR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to minimize cofounders such as increased particle load due to door opening and number of persons in the OR, those risk factors were standardized [ 19 , 21 ]. Door opening was reduced to a minimum: study nurse entered an empty OR, 2 scrub nurses entered OR to prepare surgical setting, patient and anaesthesiology team (2 persons) entered OR and surgical team entered OR.…”
Section: Methodsmentioning
confidence: 99%
“…Another factor which is often discussed but has not yet been thoroughly examined, is the turbulent air flow occurring at the margin of the LAF panel or even inside the LAF area due to obstacles. Only few studies compare concentration of suspended particles depending on position inside the LAF area or examines particles as potential bacteria carriers in the operative arthroplasty setting [ 11 , 12 , 19 ]. No study currently examines the quantitative and qualitative particle load or its distribution during total knee arthroplasty (TKA) in comparison with or without working of LAF system.…”
Section: Introductionmentioning
confidence: 99%
“…Common causes include poor ventilation in the OR, long surgery times, frequent opening and closing of the OR door, frequent visitors, frequent entry and exit of medical personnel, and the use of foreign materials [11]. The air in the OR contains dust, cotton wool, skin cells, and respiratory droplets, which can all be potentially contaminated by bacteria [10,12]. Studies have shown that increased frequency of OR door opening and staff movement reduces the efficiency of the ventilation system and significantly increases air pollution [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The air in the OR contains dust, cotton wool, skin cells, and respiratory droplets, which can all be potentially contaminated by bacteria [10,12]. Studies have shown that increased frequency of OR door opening and staff movement reduces the efficiency of the ventilation system and significantly increases air pollution [12][13][14][15]. In addition, compared to sliding doors, hinged doors have a greater risk of air pollution [16].…”
Section: Discussionmentioning
confidence: 99%
“…They supported that OR contamination was more likely attributable to the effects of the personnel who enter the OR, rather than as a primary cause of DOs. Furthermore, Rezapoor et al [25] demonstrated that the laminar airflow was protective against the negative influences of the number of people, and partially of DOs. Smith et al [13] also showed that bacteria colony forming units cultured on plates placed in sterile basins in the OR during the operation were significantly negatively associated with any DOs, and the function of laminar air flow.…”
mentioning
confidence: 99%